COMPOSITION OF TRAPPED FLUIDS IN CUBOID FIBROUS DIAMONDS FROM THE UDACHNAYA KIMBERLITE: LAM-ICPMS ANALYSIS - Zedgenizov D.A.; Shatsky V.S.; Rege S.; Griffin W.L.; Kagi H. (My University, 2007)
The bulk major- and trace-element compositions of micro-inclusions in 24 cuboid diamonds from the Udachnaya kimberlite pipe (Siberia, Russia) have been quantitatively analyzed by Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LAM-ICPMS). Micro-inclusions in the studied diamonds represent a bulk sample of the fluids from which the diamonds crystallized; they define a continuous range between magnesian and calcic carbonate-rich compositions at relatively constant Fe contents (Ca/(Ca + Mg) = 0.31–0.68; Mg/(Mg + Fe) = 0.66–0.78). In general the major- and trace-element patterns of the trapped fluids in Udachnaya cuboid diamonds are similar to those of kimberlites and carbonatites. However, some important differences are observed: (1) the fluids in diamonds are enriched in K, Na, Fe and depleted in Al relative to the host kimberlite; (2) the REE patterns of the fluids are steeper than those of kimberlites; (3) many of the fluids show strong depletion in Ti, Zr and Y.The observed geochemical features are consistent with a genetic link between the diamond-forming fluids and ephemeral carbonatitic fluids/melts which may be precursors of the host kimberlite. These fluids/melts may originate either from the metasomatic and influx of carbonatitic agents or from partial melting of previously carbonated eclogites and peridotites. Some elemental variations may be explained by fractional crystallization of such fluid/melts, or mixing between fluids with different compositions.
Keywords: CARBONATITIC MELT; DIAMOND; FLUID; KIMBERLITE; LAM-ICP-MS; TRACE ELEMENTS